From Contamination to Consequence: Tracing Donna Lake’s Human Environmental History - Dean Kyne (Geographies, 2025)
The Donna Reservoir and Canal System (Donna Lake) in Texas has been a persistent source of environmental contamination for over a century, exposing surrounding communities to dangerous levels of polychlorinated biphenyls (PCBs). Originally built for agricultural irrigation, the system became a recreational fishing site before PCB contamination was discovered during public health investigations in the 1990s. This study examines patterns of demographic vulnerability, evaluates remediation efforts by the U.S. Environmental Protection Agency (EPA), and explores residents’ ongoing challenges related to toxic exposure. Using publicly available demographic data, EPA reports, and previous health assessments, the study analyzes variations in community characteristics by proximity to Donna Lake and reviews the effectiveness of interventions implemented to date. The results show that communities closer to the contamination site are predominantly low-income and Spanish-speaking, and that remediation efforts, although initiated, have been slow and insufficient to fully eliminate health risks. The residents continue to face gaps in risk communication and protection. The findings underscore the lasting impacts of historical contamination on vulnerable populations and highlight the urgent need for more effective, community-centered remediation strategies to address persistent environmental health disparities.